a INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN LEARNING (Case Study at Assisi Fodo Private Elementary School): Indonesia - Destin Ricardo Lase; Ade Iriani; Sophia Tri Satyawati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
ITC has contributed to developing quality as well as innovation in educational institutions. Teachers and students are expected to be able to adapt and be creative in the use of ITC facilities. The purpose of this study was to see the extent to which an educational institution integrates ITC facilities in the process of learning activities in schools. This research method uses descriptive qualitative using interviews, observations, and documentation studies at SD Swasta Asisi Fodo. The technique of analyzing data is according to the Miles and Huberman method which consists of data reduction, presentation, and conclusion. The results of the study show: 1) The availability of ITC facilities and infrastructure in educational institutions allows for creativity and innovation; 2) Teachers and students can adapt to using ITC; 3) Educational institutions offer quality educational programs to the community.